A COVID-19 University-Based Dental Clinic Experience and Infection Control Protocol Modification for Safe Clinical Education - Lingawi, Hanadi S.; Aldahlawi, Salwa A.; Afifi, Ibtesam K. (European Journal of Dentistry, 2022)
Objectives The aim of the study was to share our experience of the development and application of a modified infection control protocol at the Dental Teaching Hospital, Umm Al-Qura University (UQUDENT) during the second wave of the COVID-19 pandemic. A second aim was to evaluate the impact of the implemented strategies on preparations for future requirements in clinical dental education.Materials and Methods In this descriptive study, we evaluated the challenges facing dental practice and categorized them into four domains: challenges facing dental practice during the pandemic, the risk of acquiring COVID-19 infection, the design of student clinics, and the financial challenges. The impact of strategies established to deal with such challenges was studied by comparing the number of treated patients from September 1, 2020, to March 01, 2021, with the number treated during the same months pre-COVID-19. The COVID-19 polymerase chain reaction (PCR) confirmed students and health care workers (HCWs) were expressed in numbers and percentages in each category of the study group.Results Policies were set up to deal with the challenges in each domain, after training all the hospital personnel in mitigation of the spread of infection within the hospital. We left a non-working clinic between every two operating clinics, and the patient risk was assessed by triage scoring and health status checks by a Saudi mobile application at the entrance. The hospital delivered more personal protective equipment and obligated all students and HCWs to wear KN95 or N95 masks during procedures. Over 1,500 patients were treated during the study period with more than a 30% reduction in comparison to those in the pre-COVID-19 period, but only 20 UQUDENT personnel had confirmed COVID-19 infection, and all proved to be community-acquired by contact tracing.Conclusion The measures implemented in this study proved effective. With the challenges and limited resources, UQUDENT managed to resume the operation of its dental clinics and training while preventing cross-infection, and it ensured that dental students graduated with the required competency. Sharing experiences between educational institutes will help to graduate safe competent practitioners.
Keywords: COVID-19; dental education; clinical training; contact tracing; infection control